Employment Adjustment in Portugal: Evidence from Aggregate and Firm Data - John T. Addison; Paulino Teixeira (Institute for the Study of Labor (IZA), 2001)
This paper examines the pattern of employment adjustment in Portugal. First, the issue is addressed using a long time series of aggregate data. Although the employment data show persistence, there is nonetheless a fairly rapid rate of employment adjustment. Second, a much shorter time series of firm data is used to check the persistence detected at aggregate level, and also to examine the contribution of atypical work over the cycle. Consistent with the aggregate evidence, and despite stronger employment inertia, there is no suggestion in the firm panel that labour demand is cyclically unstable.
Keywords: J32; J23; C23; C22; 330; Employment adjustment; employment protection; labor demand; errorcorrection model; panel estimation; Arbeitsnachfrage; Anpassung; Schock; Arbeitsmarktflexibilisierung; Beschäftigungseffekt; Schätzung; Portugal